2017
DOI: 10.4172/2379-1764.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Recent and the Latest Developments in Rapid and Efficient Detection of Salmonella in Food and Water

Abstract: Salmonella is a leading cause of foodborne diseases. Gastroenteritis caused by nontyphoid Salmonella is still a major infectious disease in the world. About 95% of Salmonella infections are caused by ingestion of contaminated food and water. Rapid, sensitive, and efficient detection and identification of Salmonella from foods and water are critical for minimizing the spread of outbreaks caused by this pathogen. These methods can be applied to track the food source of contamination or by early diagnosis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Apparently, to diagnose paratyphoid fever, most diagnostic microbiology laboratories depend on a conventional approach of culture and biochemical analysis, which often takes at least 4–5 days to obtain final results [ 27 ]. Although efforts have been made in the last three decades to establish accurate and responsive testing systems for Salmonella , these efforts were not focused on S. Paratyphi [ 28 , 29 , 30 ]. Since it is important to differentiate between S. Typhi and S. Paratyphi infections, as they cannot be differentiated clinically, microbial culture has been supported by other tests that are based on the detection of antigens, antibodies, or nucleic acid (i.e., RNA or DNA).…”
Section: Laboratory Diagnostic Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently, to diagnose paratyphoid fever, most diagnostic microbiology laboratories depend on a conventional approach of culture and biochemical analysis, which often takes at least 4–5 days to obtain final results [ 27 ]. Although efforts have been made in the last three decades to establish accurate and responsive testing systems for Salmonella , these efforts were not focused on S. Paratyphi [ 28 , 29 , 30 ]. Since it is important to differentiate between S. Typhi and S. Paratyphi infections, as they cannot be differentiated clinically, microbial culture has been supported by other tests that are based on the detection of antigens, antibodies, or nucleic acid (i.e., RNA or DNA).…”
Section: Laboratory Diagnostic Approachesmentioning
confidence: 99%
“…In addition to the bacterial culture of S. Paratyphi, detection and screening methods rely heavily on the Widal test, enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) [ 31 ]. However, these methods are not suitable for large scale routine screening, because it takes a few days for the confirmation of the presence of the bacteria [ 28 ]. Moreover, the methods require highly skilled laboratory personnel to handle the equipment [ 28 ].…”
Section: Laboratory Diagnostic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the traditional Salmonella culture-based approaches, several investigations have shown that qPCR methods provide superior efficiency and specificity in detecting SE in a variety of food matrices, including shell eggs [16,18,19]. Nevertheless, DNA from dead cells may be falsely perceived as a positive readout of viable bacteria and result in an overestimation of the viable cell numbers [20]. These qPCR tests may also be affected by the inhibitory effects of food components, which can lead to false negative results and increase the risk of contracting foodborne illnesses if contaminated food is consumed [21].…”
Section: Introductionmentioning
confidence: 99%